Extratemporal abnormalities in phosphorus magnetic resonance spectroscopy of patients with mesial temporal sclerosis - Park, Eun Joo; Garcia Otaduy, Maria Concepcion; Lyra, Katarina Paz de; Andrade, Celi Santos; Martins Castro, Luiz Henrique; Passarelli, Valmir; Figueiredo Valerio, Rosa Maria; Jorge, Carmen Lisa; Tsunemi, Miriam Harumi [UNESP]; Leite, Claudia da Costa (Assoc Arquivos Neuro- Psiquiatria, 2016)
Objective: We evaluated extratemporal metabolic changes with phosphorus magnetic resonance spectroscopy (P-31-MRS) in patients with unilateral mesial temporal sclerosis (MTS). Method: P-31-MRS of 33 patients with unilateral MTS was compared with 31 controls. The voxels were selected in the anterior, posterior insula-basal ganglia (AIBG, PIBG) and frontal lobes (FL). Relative values of phosphodiesters-PDE, phosphomonoesters-PME, inorganic phosphate - Pi, phosphocreatine-PCr, total adenosine triphosphate [ATP(t=) gamma- + a- + b-ATP] and the ratios PCr/ATP(t), PCr/gamma-ATP, PCr/Pi and PME/PDE were obtained. Results: We found energetic abnormalities in the MTS patients compared to the controls with Pi reduction bilaterally in the AIBG and ipsilaterally in the PIBG and the contralateral FL; there was also decreased PCr/gamma-ATP in the ipsilateral AIBG and PIBG. Increased ATP(T) in the contralateral AIBG and increased gamma-ATP in the ipsilateral PIBG were detected. Conclusion: Widespread energy dysfunction was detected in patients with unilateral MTS.
Keywords: phosphorus spectroscopy; magnetic resonance imaging; neurometabolism; mesial temporal sclerosis; epilepsy